A Case Study on the Strategy of Bank Negara Malaysia to Curb Loan Growth - Mohd Kassim, Radzuan (1997)
1997 was a challenging year for the con duct of monetary policy. The first quarter of the year saw high levels of monetary growth driven by rapid growth in credit, which had also prevaile d during the most part of 1996. In addition, loans were increasingly channelled towards less productive activities. Such developments raised several concerns. High levels of monetary expansion, if left unchecked, would have inflationary implications on the economy. Furthermore, the rise in loans to the property sector and to stock market-related activities increase d the exposure of banking institutions to these sectors, raising the potential risk to the soundness of the institutions. Given these concerns, Bank Negara Malaysia (BNM) has to introduce strategic measures, to ensure that the stability of the banking system was not undermined by excessive exposure to the relatively more volatile sectors of the economy.